How to move towards One Health surveillance? A qualitative study exploring the factors influencing collaborations between antimicrobial resistance surveillance programmes in France - Bourély, Clémence; Rousset, Léo; Colomb-Cotinat, Mélanie; Collineau, Lucie (Frontiers in Public Health, 2023)
Antimicrobial resistance (AMR) is a major public health issue, against which international organisations and governmental bodies call for integration between surveillance programmes involved in human, animal, and environmental sectors. Collaborations are the primary feature of integration and deserve to be supported. However, little is known about the factors that can foster collaborations between surveillance programmes. This study aimed to provide a better understanding of the factors for setting-up collaborations between AMR surveillance programmes in France. We performed a qualitative study based on 36 semi-structured interviews with programmes’ coordinators and 15 with key-informant experts involved in AMR surveillance. The implementation of collaboration between sectors was multifactorial: we identified 42 factors grouped into six categories (i.e. characteristics of the overall AMR surveillance system, features of the collaborating programme, profile of the actors involved, characteristics of the collaboration itself, broader context, and AMR research activities). Collaborations were mainly fostered by good interpersonal relationship between actors, their interest in transdisciplinary approaches and the benefits of collaboration on the programmes involved. Limited resources and the complexity of the AMR surveillance system hindered collaboration. Paradoxically, coordinators generally did not perceive collaborations as a resource-pooling tool since they generally set them up only after consolidating their own programme. Since most factors identified were not specific to AMR, these results can be useful for other collaborative surveillance system. Ultimately, they provide a better understanding of stakeholders’ motivations and influences driving collaboration, and can help researchers and risk managers promoting a One Health approach against public health threats.